Implementation of core values in the context of performance: a Makassar City Government study - Tintin Sri Murtinah; Bambang Giyanto; Arifiani Widjayanti (Publisia: Jurnal Ilmu Administrasi Publik, 2024)
The implementation of core moral values, particularly AKHLAK, among government employees plays a crucial role in enhancing public service qualityand reinforcing employer branding. This study examines the efficacy ofAKHLAK implementation among Makassar City’s Administrative Civil Ser-vants (ASN) as fundamental principles in delivering effective and focusedpublic services. Utilizing focus group discussions, documentation analysis,and Grindel’s framework of policy implementation, this research explores theimpact of Menpan RB Circular Letter No. 20 of 2021 on AKHLAK implementation. Key findings indicate that the promotion of AKHLAK has significantlyimproved employee discipline and public service standards in Makassar City.Supported by institutional backing and adequate infrastructure, the city government demonstrates a robust commitment to fostering AKHLAK valuesamong its employees. The study concludes that Makassar City has achievedconsiderable success in implementing and sustaining AKHLAK principles,contributing to notable advancements in governmental service delivery andoverall civic compliance. Overall, this research confirms Makassar City’sachievements in integrating and maintaining AKHLAK values, thereby con-tributing to a more effective and responsive governance framework